Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Bahir Dar University - International Livestock Research Institute; Bahir Dar University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Bahir Dar University. MOU signed on December 23, 2021 by Jimmy Smith, Director-General of ILRI and Firew Tegene, President of Bahir Dar University.